Lipase-Catalyzed Interesterification for the Synthesis of Medium-Long-Medium (MLM) Structured Lipids: A Review - Sitanggang, Azis Boing; Adawiyah, Dede Robiatul; Hariyadi, Purwiyatno; Utama, Qabul Dinanta (Food technology and biotechnology, 2019)
Medium-long-medium (MLM) structured lipids typically contain medium-chain fatty acids (C6-C12) at sn-1,3 and long-chain fatty acids (C14-C24) at sn-2 positions. They have reduced calories and are suitable for the control of obesity, lipid malabsorption and other metabolic disorders. This review focuses on the synthesis of MLM lipids by the enzymatic interesterification. It gives detailed description of biocatalysts, substrates, reactors and synthesis methods, and discusses the use of MLM lipids in food products. The information provided in this review can be considered as the current state-of-the art for developing a future strategy for the synthesis of MLM structured lipids.